2018
DOI: 10.26906/sunz.2018.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Дослідження Методів Побудови Рекомендаційних Систем В Мережі Інтернет

Abstract: У роботі розглянуті основні види рекомендаційних систем у мережі Інтернет, засновані на методахконтентної та колаборативної фільтрації. Розглянуто способи збору даних про користувачів з вебресурсів, необхідні для формування рекомендацій. Досліджено методи побудови класифікаторів для контентної фільтрації. Також досліджено способи обчислення коефіцієнту подібності користувачів абооб’єктів у колаборативній фільтрації.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Analysis of the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] showed that there are currently many methods and models for improving the quality of recommendation systems. One of the main ways to achieve this is to use hybrid RSs.…”
Section: Quality Characteristics Of Recommendation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] showed that there are currently many methods and models for improving the quality of recommendation systems. One of the main ways to achieve this is to use hybrid RSs.…”
Section: Quality Characteristics Of Recommendation Systemsmentioning
confidence: 99%
“…In neighborhood-based models of recommendation systems [1][2][3][4][5], the creation of a user recommendation list can be divided into three separate processes:…”
Section: Quality Characteristics Of Recommendation Systemsmentioning
confidence: 99%
“…На відміну від моделей РС на основі сусідства, які використовують коефіцієнти подоби для створення списків рекомендацій, факторизаційні моделі виявляють та використовують приховані фактори (ПФ), що впливають на вподобання користувачів [1][2][3].…”
Section: вступunclassified
“…x -the value of the i-th attribute, respectively, in the 1st and 2nd objects; 1 Х , 2 Х -the set of values of attributes in the 1st and 2nd objects.…”
Section: ( ) D X X -The Distance Between Objectsmentioning
confidence: 99%
“…One of the basic algorithms for building recommendation systems is collaborative filtration [1,2]. It is based on the calculation of similarity coefficients between users to find a most similar users and objects.…”
Section: Introductionmentioning
confidence: 99%